Respons Tiga Varietas Tomat (Lycopersicum esculentum Mill) Akibat Pemberian Volume Air - Mukarromah, Wahdaniatul; Santoso, Juli; Moeljani, Ida Retno (JURNAL AGROTROPIKA, 2024)
Drought is one of the factors in tomato (Lycopersicum esculentu Mill.) crop failure which is often found in Indonesia. Planting drought-resistant varieties is a solution to increase the productivity of tomato to meet market demand. The research was carried out in the Kumendung Hamlet Plastic House, Ngembung Village, Cerme District, Gresik Regency at an altitude of 4 meters above sea level with an average temperature of around 25º - 34º C. This research was conducted using a factorial of Completely Randomized Design (CRD). The first factor is application water volume with 3 levels, namely: C0 = water content 100% field capacity (control); C1 = water content 75% field capacity; C2 = water content 50% field capacity. The second factor is tomato varieties with 3 levels, namely: V1 = Servo Variety; V2 = Tymoti variety; V3 = Tantyna variety. The research data were analyzed using Analysis of Variance (ANOVA), then the Least Significant Difference (LSD) test was carried out at a test level of 5%. The results showed that it was no interaction between the application of water volume and the tomato varieties. Applying water 828,75 ml or 75% of field capacity and using the Tymoti tomato variety gave the best results in terms of number of leaves, number of flowers, number of fruit, and fruit weight per plant. The Tymoti tomato variety gave the shortest flowering period. Key Words: Drought, tomatoes, varieties, watering